Fertilizers Effect Blue Green Algae and increasing their Toxins - Jessim, Ahmed Ibrahim (International Journal of Bio-resource and Stress Management, 2018)
Urban activities add pollutants to the environment, and increase Phosphorous [P], Nitrogen [N], Sulfate [S] and Iron [Fe], these pollutants in Aquatic environment can cause Eutrophication of Blue green algae (BGA), which they are an auto nutrition organisms via photosynthesis and organic materials, prokaryotic and they have not specialized organelles and produce phycocyanin pigment which it’s just in cyanobacteria, which have been recognized in different environments such as Antarctica below 0 °C also in spring. Many species can produce toxic substances which they are secondary metabolic products, formed by cyanobacteria, these toxins can cause humans toxication, in different parts of the world which is an evidence of algal toxins accumulation in treated drinking fresh water, and can cause neurosystem illness and digestion system especially Hepatic also dermatitis, algal toxins represent an international problem in all water types salty, brackish and fresh water, also can be produced by terrestrial species. These types of toxins found in all types of waters fresh, brackish and salty waters. Most of these toxins are carcinogenic, many countries needs to go on to monitor this phenomenon and limitation of toxic species with fixation of routine tests for drinking water. Impact of health in more by exposure to the toxins and keep water safety imposes its presence through the permanent observer and early monitoring. Non floating algae on the surface of water let us judge on being free of algae. Sometimes one alga can produce more than one type of toxins and many species can produce one type of toxin.